AN EMPIRICAL ANALYSIS OF SUKUK ISSUANCE AND GOOD CORPORATE GOVERNANCE (GCG) AS DETERMINANTS OF CORPORATE PROFITABILITY IN IDX-LISTED FIRMS - Zhohra, Fatimah; Malahayatie, Malahayatie; Rofizar, Heny (J-ISCAN: Journal of Islamic Accounting Research, 2025)
Profitability as one of the key benchmarks for measuring a firm’s earnings, is crucial for determining whether the company has operated its business efficiently. Profitability ratios also serve as measurement tools used to assess a company’s effectiveness in generating profits. One such ratio is Return on Equity (ROE), which is considered one of the cleanest measures of return. Among the investment products currently developing in the Islamic capital market is sukuk. Through sukuk, a company can obtain funding sources and potentially generate profits. Sukuk serve as an alternative for companies to attract investors to commit their capital, and every company is required to implement Good Corporate Governance (GCG) to sustain its long-term viability. This study employs a causative quantitative approach, with data processed using the E-Views application. The sample consists of 27 companies. The sampling technique used in this study is the purposive sampling method. The selected companies are those listed on the Indonesia Stock Exchange (IDX) during the 2017–2021 period, resulting in a total sample of 27 companies. The partial test results indicate that sukuk issuance has no significant effect on profitability. In contrast, Good Corporate Governance (GCG) exhibits a negative effect on firm profitability. However, the simultaneous analysis reveals that sukuk issuance and GCG jointly exert a positive influence on corporate profitability.